Effect of processing on phenol content, and acceptability of camu camu peel and seed infusions (Myrciaria dubia) - Escudero Shuña, Peggy (2023)
In the camu camu (Myrciaria dubia) processing, the peels and seeds are the main residues with a high potential for use as they contain anthocyanins (peel) and phenolic compounds. The objective of this research was to take advantage of camu camu peels and seeds as ingredients for infusion filters, and to evaluate the effect of drying. First, the peels and seeds were dehydrated at three temperatures (50, 65 and 70°C) and characterized in total anthocyanins and total phenolic compounds. Then, they were sieved considering two size ranges: small (between 0.1 and 0.475 cm) and large (larger than 0.475 cm) to be evaluated sensorially by a trained panel as an infusion, using a hedonic scale of general acceptability of 10 cm. The results showed that the peels contain anthocyanins and a higher content of phenolic compounds. In the case of the sensory evaluation, the panel preferred the large-range size, since they facilitate the packaging of the filters and better dose the dissolution of compounds in the medium (hot water) compared to the small-range size. The selected drying temperature was 65°C, since some characteristics were significantly the same as 50°C, and the drying time is shorter. In addition, the potential use of the seed for other formulations was observed since it does not give extreme flavors and increases the body of the beverage.